RETENTION OF NAPHTHALENE ON FUNCTIONALIZED ANIONIC CLAYS RÉTENTION DU NAPHTALÈNE SUR DES ARGILES ANIONIQUES FONCTIONNALISÉES - MADALINA-ŞTEFANIA PIRVAN; Rachid Brahmi; Laurence Pirault-Roy; Ileana Denisa Nistor (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In this work, we studied the retention of naphthalene from liquid effluents, on anionic clays of Doubled Hydroxides Lamellar (LDHs) type and functionalized with organic substances. Naphthalene is a polycyclic pollutant, which can result from various industries such as the plastics industry (PVC), dyes, adhesives, insecticides and others. Polycyclic pollutants are toxic and not degradable and can affect human health as well as the balance of ecosystems and the environment. To remedy this pollution and to allow retention of naphthalene, we have studied different adsorbent materials such as functionalized anionic clays by adding β-Cyclodextrin to obtain an organophilic material. We therefore prepared samples of Mg-Al anionic clays in a 3 : 1 ratio, called LDHs and β-Cyclodextrin was intercalated to obtain functionalized LDHs, named β-CD-LDH. We then determined the best operating conditions (quantity of material, contact time, pH) in order to maximize the amount of retained naphthalene.